Design and control of small DC-link capacitor-based three-level inverter with neutral-point voltage balancing - In, Hyo Chul; Kim, Seok Min; Lee, Kyo Beum (Energies, 2018)
This paper presents a method to improve the quality of input-output currents in a three-level neutral-point clamped (NPC) inverter with small direct current-link (DC-link) capacitor systems. The inverter systems with the small DC-link capacitors have several advantages in terms of cost, volume, life-time, and reliability when compared to inverters that use large DC-link capacitors. However, there are problems with respect to the deterioration of the input current quality and a severe ripple of neutral-point voltage (NPV), which can cause an aggravated output current. To mitigate these issues, an additional circuit is applied for the input current shaping and a compensation algorithm is applied to reduce the ripple voltage of NPV. The effectiveness of the proposed design and control method is verified with various simulation and experimental results.
Keywords: Carrier-based pulse-width modulation (CB-PWM); Electrolytic capacitor-less; Grid current; Input current qualities; Neutral point clamped inverters; Neutral-point voltage balancing; Neutral-point voltages; Three level neutral point clamped (NPC) inverter; Carrier-based pulse-width modulation (CB-PWM); Electrolytic capacitor less inverter; Grid current quality; Neutral-point clamped inverter